2003
DOI: 10.1046/j.1471-4159.2003.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and behavioural effects of the adenosine A2a receptor antagonist KW‐6002 in a rat model of l‐DOPA‐induced dyskinesia

Abstract: We have examined the ability of KW-6002, an adenosine A 2a antagonist, to modulate the dyskinetic effects of L-DOPA in 6-hydroxydopamine-lesioned rats. In animals rendered dyskinetic by a previous course of L-DOPA treatment, KW-6002 did not elicit any abnormal involuntary movements on its own, but failed to reduce the severity of dyskinesia when coadministered with L-DOPA. A second experiment was undertaken in order to study the effects of KW-6002 in L-DOPA-naive rats. Thirty-five animals were allotted to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(100 citation statements)
references
References 39 publications
10
89
1
Order By: Relevance
“…Thus, repeated L-DOPA treatment in Pitx3 ak/ak mice, which produces LID, correlates with increased ERK phosphorylation in striatal cholinergic interneurons and a decrease in MSN. To further confirm the correlation of ERK phosphorylation in striatal cholinergic neurons with L-DOPA-induced behavioral expression of dyskinesia, we used a selective A2A receptor antagonist, which ameliorates akinesia in human PD patients without producing dyskinesia after repeated treatment (22). The selective A2A antagonist, KW-6002, significantly improved akinesia in Pitx3 ak/ak mice, as evidenced by both open-field test and rearing activity (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, repeated L-DOPA treatment in Pitx3 ak/ak mice, which produces LID, correlates with increased ERK phosphorylation in striatal cholinergic interneurons and a decrease in MSN. To further confirm the correlation of ERK phosphorylation in striatal cholinergic neurons with L-DOPA-induced behavioral expression of dyskinesia, we used a selective A2A receptor antagonist, which ameliorates akinesia in human PD patients without producing dyskinesia after repeated treatment (22). The selective A2A antagonist, KW-6002, significantly improved akinesia in Pitx3 ak/ak mice, as evidenced by both open-field test and rearing activity (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Their use of a different psychostimulant drug and paradigm of sensitization, as well as an A 2A agonist (which may be less relevant to endogenous adenosine actions on CNS A 2A Rs than are A 2A antagonists) could account for the difference in results. Moreover, although Lundblad et al (2003) have confirmed that treatment of 6-OHDA-lesioned rats with an adenosine A 2A antagonist alone did not elicit any abnormal involuntary movements while relieving motor disabilities, they did not observe any effect of KW-6002 on the severity of dyskinesias when it was coadministered with L-dopa. Another study of unilaterally 6-OHDA-lesioned rats found that an A 2A antagonist reversed but did not prevent L-dopa-induced motor alterations (Bove et al, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…Changes in the expression of presumably postsynaptic A 2A Rs after repeated dopaminergic exposures might also play a functional role in the nucleus accumbens or dorsal striatum (Zeng et al, 2000;Calon et al, 2004;Tomiyama et al, 2004). Potential downstream postsynaptic mediators of sensitization that are also known to be regulated by the A 2A R include cytoplasmic signal transducers (eg dopamineand cAMP-regulated phosphoprotein of 32 kDa or DARPP-32) and nuclear transcriptional targets (eg DFosB, enkephalin, and dynorphin gene expression in striatal neurons; Fienberg et al, 1998;Canals et al, 2003;Lundblad et al, 2003;Hakansson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…without L-Dopa) in preclinical models. A 2A antagonists have been shown to be efficacious against haloperidolinduced catalepsy [16,20,50] and showed positive effects in the forepaw stepping test in unilaterally 6-OHDA lesioned rats [51] and in the rotarod test [52]. However, most studies failed to demonstrate a significant effect of A 2A receptor antagonists on the level of contralateral rotation in lesioned rats in the absence of L-Dopa [14][15][16]53].…”
Section: Discussionmentioning
confidence: 99%